Challenges and Benefits of Conducting Environmental Justice Research in a School Setting. (August 2014) - Guidry, Virginia T.; Lowman, Amy; Hall, Devon; Baron, Dothula; Wing, Steve
Environmental justice (EJ) research requires attention to consequences for research participants beyond those typically considered by institutional review boards. The imbalance of power between impacted communities and those who create and regulate pollution creates challenges for participation, yet research can also benefit those involved. Our community-academic partnership designed the Rural Air Pollutants and Children's Health (RAPCH) study to provide positive impacts while measuring health effects at three low-resource public middle schools near concentrated animal feeding operations (CAFOs) in North Carolina. We evaluated perceived benefits and challenges of study involvement by interviewing school staff and community liaisons who facilitated data collection. Reported benefits included enhancement of students' academic environment and increased community environmental awareness; challenges were associated mainly with some participants' immaturity. Leadership from a strong community-based organization was crucial to recruitment, yet our approach entailed minimal focus on EJ, which may have limited opportunities for community education or organizing for environmental health.